Expression of MACC1 protein in gastric cancer and its effect on proliferation and invasion of gastric cancer cells - Zheng, Gang; You, Changjiang; Qiu, Zhidong; Zheng, Xiannian (Cellular and Molecular Biology, 2020)
To detect the expression of metastasis-associated colon cancer gene 1 (MACC1) protein in gastric cancer tissues, and analyze its relationship with clinicopathological parameters of gastric cancer and its effect on proliferation and invasion of gastric cancer cells. Methods: 71 patients with gastric cancer in Fifth Hospital in Wuhan from June 2014 to March 2018 were selected as research subjects. Western blot was used to detect the expression of MACC1 in gastric cancer tissue and normal gastric mucosa tissue, and gastric cancer cell SGC7901 was transfected. Transfection group (transfected with MACC1-siRNA), negative control group (transfected with siRNA-NC) and blank control group (untreated cells) were set up. After transfection, the expressions of MACC1 protein and mRNA in the 3 groups were detected by Western blot and qRT-PCR methods, the cell proliferation was detected by MTT method, and the invasion ability of cells in vitro was detected by Transwell chamber. Results: The expression of MACC1 protein in gastric cancer tissue was higher than the control group (P< 0.05). The expression of MACC1 protein in gastric cancer was related to the differentiation degree, infiltration depth, lymph node metastasis and different stages of gastric cancer (P< 0.05). After transfection, the expressions of MACC1 protein and mRNA in the transfection group was significantly lower than the negative control group and blank group (P< 0.05). There was no significant difference in cell viability between the blank group and negative control group at each time point (P> 0.05). Conclusion: MACC1 was highly expressed in gastric cancer tissues. The expression of MACC1 was related to the differentiation degree, infiltration depth, lymph node metastasis and staging of gastric cancer. Down-regulation of MACC1 could inhibit the proliferation and invasion of gastric cancer cells. This study provided a certain biological basis for early clinical prediction, diagnosis and treatment of gastric cancer.